Study of cavitation in hydro turbines - a review - Pardeep, Kumar; R.P., Saini (ELSEVIER, 2009)
Reaction turbines basically Francis turbines and propeller/Kaplan turbines are suitable for medium and low head hydropower sites. The management of the small hydropower plants is an important factor, for achieving higher efficiency of hydro turbines with time. Turbines show declined performance after few years of operation, as they get severely damaged due to various reasons. One of the important reasons is erosive wear of the turbines due to cavitation. Reaction turbines, however are more prone to cavitation especially Francis turbines where a zone in the operating range is seriously affected by cavitation and considered as forbidden zone. Cavitation is a phenomenon which manifests itself in the pitting of the metallic surfaces of turbine parts because of the formation of cavities. In the present paper, studies undertaken in this field by several investigators have been discussed extensively. Based on literature survey various aspects related to cavitation in hydro turbines, different causes for the declined performance and efficiency of the hydro turbines and suitable remedial measures suggested by various investigators have been discussed